Functional magnetic resonance imaging activation for different vergence eye movement subtypes. (26th October 2022) - Fogt, Nick; Toole, Andrew J.; Li, Xiangrui; Owusu, Emmanuel; Manning, Steven T.; Kulp, Marjean T.
Abstract: Introduction: Maddox suggested that there were four convergence subtypes, each driven by a different stimulus. The purpose of this study was to assess the neural correlates for accommodative convergence, proximal convergence (convergence stimulus provided), disparity convergence and voluntary convergence (no specific convergence stimulus provided) using functional magnetic resonance imaging (fMRI). Methods: Ten subjects (mean age = 24.4 years) with normal binocular vision participated. The blood oxygenation level‐dependent (BOLD) signals of the brain from fMRI scans were measured when subjects made vergence eye movements while: (1) alternately viewing letters monocularly where one eye viewed through a −2.00 D lens, (2) alternately viewing Difference of Gaussian targets monocularly at distance and near, (3) viewing random dot stereograms with increasing disparity and (4) voluntarily converging the eyes with binocular viewing. Results: The accommodative convergence paradigm resulted in activation on the right side in the right fusiform cortex and the right middle occipital cortex. The proximal convergence stimulus mainly activated areas in the right occipital lobe. The disparity stimulus activated areas in the left occipital cortex and the left frontal cortex. Finally, the voluntary convergence paradigm resulted in activation primarily in the occipital lobe and mostly bilaterally. Conclusion: The accommodative, proximal, disparity and voluntary convergence paradigms resulted in activation in unique areas in the brain with functional MRI. Activation was found in more areas in the proximal and voluntary conditions compared with the accommodative and disparity conditions.